Molecular dynamics simulation of Fe-NO2 At-alpha mangostin as radiopharmaceutical model for detection of fatty acid synthase in cancer - N Elly Rosilawati; Muhamad Yusuf; Achmad Hussein S. Kartamihardja; Shaharum Samsuddin; Muchtaridi Muchtaridi (Wolters Kluwer Medknow Publications, 2021)
α-mangostin is a xanthone compound isolated from mangosteen pericarp. It is known as an anticancer through induction of apoptotic process by inhibiting fatty acid synthase (FAS) receptor. α-mangostin is a potentially useful ligand for diagnostic purposes in the form of complexes with a radionuclide such as 68Gallium (68Ga). Unfortunately, α-mangostin could not be directly labeled with radionuclides. In order to be labeled, a chelator such as 1,4,7-triazacyclononane-1,4,7-triacetic acid (NOTA), a derivative (NO2At), is required. The aim of this study was to find out the interaction of Fe-NO2At-α-mangostin complex compound against FAS receptor using molecular dynamics software. Both the metals have similar chemical characteristics. The results showed a strong interaction between Fe-NO2At-α-mangostin complex compound and FAS receptor. The molecular dynamic showed the complex compound Fe-NO2At-α-mangostin in FAS-KS which produced a bond-free energy values (ΔG) of − 96.7 kcal/mol, forming hydrogen bonds with amino acid residues Glu 115 and Ser 114. The model of molecular dynamic result could be used as a model for the production of 68Ga-α-mangostin in radiopharmaceutical.